Pengaruh Profitabilitas, Leverage, Kepemilikan Manajerial, dan Kepemilikan Institusional terhadap Harga Saham - Rachmatika Irfani; Muhammad Anhar (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2019)
Managerial Ownership, and Institutional Ownership of Stock Prices in Manufacturing Companies listed on the Indonesia Stock Exchange in 2015-2017 with a total sample of 35 companies. The results showed that profitability had an effect on stock prices, managerial ownership had an effect on stock prices, while institutional ownership and leverage had no effect on stock prices. Simultaneously, profitability, leverage, managerial ownership, and institutional ownership affect stock prices.